Respuesta :

Answer:

Step-by-step explanation:

If we are looking for the composition of f(g(7)), we will start at the innermost part of the problem, which is to evaluate g(7).  That means that we put 7 in for x in the g function and come up with a solution to that first.

If g(x) = x - 3, then g(7) = 7 - 3 which is 4.  Now take that 4 and put it in for x in the f function:

f(4) = [tex](4)^2+4[/tex] which is 16 + 4 which is 20

Therefore, f(g(7)) = 20

Answer:

If we are looking for the composition of f(g(7)), we will start at the innermost part of the problem, which is to evaluate g(7).  That means that we put 7 in for x in the g function and come up with a solution to that first.

If g(x) = x - 3, then g(7) = 7 - 3 which is 4.  Now take that 4 and put it in for x in the f function:

f(4) =  which is 16 + 4 which is 20

Therefore, f(g(7)) = 20

Step-by-step explanation: